(untitled) (KONFERENSIYA, 2025)
This article examines the communicative and functional features of medical texts in English and Uzbek. Medical texts serve multiple purposes, including providing information, giving instructions, expressing professional evaluation, maintaining communication, clarifying terminology, and linking language to factual reality. Examples illustrate the use of specialized terminology, native equivalents, compound forms, and patient-oriented expressions. The study highlights the importance of these features for translation, clinical practice, patient education, and terminology standardization. Findings show that English texts are concise and rely on international terminology, while Uzbek texts often provide additional explanation for better patient understanding, demonstrating the role of cultural adaptation and functional purpose in medical communication